A study of outpatient healthcare use by ageing people with HIV. Issue 3 (4th May 2019) - Geys, Michèle; Remmen, Roy; Apers, Ludwig
Abstract: Background : Antiretroviral treatment has turned HIV infection into a chronic condition with a near normal life expectancy and an ageing patient population. For a well-defined proportion of these patients, HIV-care could pass from specialty care to primary care, especially for prevention and treatment of additional chronic diseases. A better understanding of the complex health needs of this particular proportion is needed to determine the optimal way to integrate specialist and primary care. Objectives : Our objective was to examine the health-seeking behaviour of ageing HIV patients. We investigated which physicians they consulted and the reasons for encounter. We also explored patients' participation in preventive healthcare activities. Methods : We conducted a retrospective descriptive cohort study among adults, 60 years of age or older living with HIV, who came for a routine consultation visit at the HIV clinic of the Institute of Tropical Medicine (ITM) over a period of 9 months. Those who met the inclusion criteria were offered a self-administered questionnaire. The responses were manually coded, exported into Excel and subsequently imported into SPSS for descriptive statistical analysis. Results : We analysed questionnaires from 74 patients, 11 women and 63 men. Since their last consultation visit at the ITM, 48 patients consulted their general practitioner (GP), 35 patients consulted a specialist and 7 went to the emergency department over a period of 6 months. Forty-nine patients (66%) had done a faecal occult blood test and 8 women (73% of female patients) had a screening mammography in the past 2 years, 8 women (73% of female patients) had a PAP smear in the past 3 years. Sixty-three participants (85%) declared that their vaccinations were up-to-date. Thirty-eight patients (51%) take antihypertensive medication, 35 patients (47%) cholesterol medication and 9 participants (12%) are on oral antihyperglycemic medication. Conclusions : A large proportion of patients are seeking healthcare from their GP and specialists, other than the HIV specialist. They do so both for curative and preventive health needs. This calls for a more structured collaboration between the various care providers, whereby communication plays a pivotal role.